2014
DOI: 10.1590/0103-0582201432213213
|View full text |Cite
|
Sign up to set email alerts
|

Congenital heart disease and chromossomopathies detected by the karyotype

Abstract: OBJECTIVE: To review the relationship between congenital heart defects and chromosomal abnormalities detected by the karyotype. DATA SOURCES: Scientific articles were searched in MEDLINE database, using the descriptors "karyotype" OR "chromosomal" OR "chromosome" AND "heart defects, congenital". The research was limited to articles published in English from 1980 on. DATA SYNTHESIS: Congenital heart disease is characterized by an etiologically heterogeneous and not well understood group of lesions. Several rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 52 publications
0
2
1
2
Order By: Relevance
“…COA is noted to have associated abnormalities prevalence in the range of 20–30% of which Turner and Noonan syndrome were noted to be common occurrences [12, 19, 24]. However, in our analysis, the overall prevalence of NC/GA/S in neonates with COA was 15.6%, with 4% having a diagnosis of Turner syndrome.…”
Section: Commentcontrasting
confidence: 58%
See 1 more Smart Citation
“…COA is noted to have associated abnormalities prevalence in the range of 20–30% of which Turner and Noonan syndrome were noted to be common occurrences [12, 19, 24]. However, in our analysis, the overall prevalence of NC/GA/S in neonates with COA was 15.6%, with 4% having a diagnosis of Turner syndrome.…”
Section: Commentcontrasting
confidence: 58%
“…Prior studies have evaluated overall prevalence of extracardiac abnormalities in CHD, with reported estimates in the range of 25–30% [8–12]. More recent meta-analyses and population-based studies have found a prevalence of associated anomalies in the range of 17–28% [1319]. …”
mentioning
confidence: 99%
“…Karyotyping and chromosomal microarray (CMA) methods have been used to identify the number of abnormal chromosomes and copy number variants (CMV), respectively [158][159][160]. These methods are used widely for the diagnosis of fetal aneuploidy.…”
Section: Chromosomal Abnormalities Copy Number Variants and Chdsmentioning
confidence: 99%
“…A importância desse diagnóstico é determinar a etiologia, caso necessário um aconselhamento genético é feito baseado na chance de recorrência da CC. (TREVISAN et al, 2014).…”
Section: Discussionunclassified